Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Serta Implikasinya Terhadap Produktivitas Karyawan PT. Denso Indonesia Departemen Production Control dan Logistic - Pudji Astuty; Rina Fauziah Rachman (Jurnal Manajemen FE-UB, 2021)
This study aims to determine the extent of the influence of organizational culture, leadershipstyle on employee performance through job satisfaction at PT. Asuransi Jasa Indonesia (Persero)Head Office.The data used in this study is primary data collected from respondents' answers based onthe questionnaire given, which is as many as 100 people. The data processing method uses thepath analysis method with the help of SPSS version 22.0. Statistical testing used individualparameter significance test (t test) and simultaneous significance test (F test).The results showed that simultaneously the variables of organizational culture, leadershipstyle and job satisfaction have a significant effect on employee performance. Partially it showsthat analysis 1: organizational culture variables have a significant effect on employeeperformance, while analysis 2: leadership style variables have a significant effect on employeeperformance and in analysis 3: job satisfaction variables have a significant effect on employeeperformance.Keywords: Organizational culture, leadership style, job satisfaction and employee performance1